2007
DOI: 10.1590/s0102-86502007000300006
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between textured silicone implants and those bonded with expanded polytetrafluoroethylene in rats

Abstract: Comparison between textured silicone implants and those bonded with expanded polytetrafluoroethylene in ratsComparison between textured silicone implants and those bonded with expanded polytetrafluoroethylene in rats ABSTRACT Purpose:Comparison of the inflammatory reaction promoted by textured silicone implants and that caused by the implant bonded with e-ptfe. Methods: One-hundred and fifty rats were divided into three equal groups (control, silicone, and bonded e-ptfe). These groups were subdivided into fiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
6
2
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 19 publications
7
6
2
1
Order By: Relevance
“…To compare the inflammatory reaction caused by the implant of textured silicone with the same reaction caused by the implant of textured silicone covered by E-PTFE Haddad Son et al 26 observed that both induced chronic inflammatory reaction and weak inflammatory reaction type strange body similar to the present study.…”
Section: Resultssupporting
confidence: 81%
“…To compare the inflammatory reaction caused by the implant of textured silicone with the same reaction caused by the implant of textured silicone covered by E-PTFE Haddad Son et al 26 observed that both induced chronic inflammatory reaction and weak inflammatory reaction type strange body similar to the present study.…”
Section: Resultssupporting
confidence: 81%
“…This study suggests the hypothesis that there might be less contraction in the textured prostheses due to the decrease of adhesive capsular characteristic, thus decreasing the mechanical friction previously mentioned 9,14 . The necessary force to loosen the membrane´s periimplant tissue indirectly demonstrated the invasion of this tissue inside the coating's texture.…”
Section: Discussionsupporting
confidence: 60%
“…However, polyurethane is responsible for intense inflammatory reaction, with relevant lining phagocytosis and lining degradation, making its removal difficult when it is necessary 8 . Haddad Filho et al 9 confirm that one of the most significant modifications in silicone implants was the texture of their surfaces.…”
Section: Introductionmentioning
confidence: 96%
“…Disagreeing with Haddad Filho et al 16 that found greater number of capillaries in the textured and PTFE-E groups in relation to the control group with statistical significance in various subgroups, in this study all rats that took part in the textured group had absence or discrete presence of this variable with no significant difference.…”
Section: Evaluation Of Neoangiogenesissupporting
confidence: 42%
“…According to Ratner 15 Haddad Filho et al 16 after comparing silicone implants with a textured surface and coated PTFE-E, it was concluded that both groups induced a weak foreign body reaction, which was higher in textured group. Disagreeing with this author, in this study the foreign body reaction was absent in the textured group at all subgroups.…”
Section: Evaluation Of Foreign Body Reactionmentioning
confidence: 99%